On the issue of pedagogical research in social science didactics - Staněk, Antonín (Civilia, 2025)
The theoretical study reflects the issue of pedagogical research in the subject didactics of social sciences and its impact on the development of this academic discipline. The introductory part of the study is devoted to a description of the current state of citizenship education in the context of the ongoing revision of curricular documents for primary education. The fact that citizenship education is undergoing its "Copernican turn", which is reflected both in educational practice and in the current RVP ZV, as well as in the draft of the revised curricular document, exposes the problem of the lack of relevant data from pedagogical research on key phenomena. In the second part of the study, based on an analysis of the approaches of the subject didactics of history and with regard to the fact that the subject didactics of social sciences has two theoretical levels from a general perspective, it defines and characterizes possible research areas in the subject didactics of social sciences. The third part of the study draws attention to the limits and possible obstacles associated with the perception of the subject didactics of social sciences and its own research field.
Keywords: subject didactics of social sciences; citizenship education; civic education; pedagogical research